Association of Low-Birthweight Incidence with Hemoglobin Levels in Pregnant Women at Puskesmas Demangan, Madiun In 2022 - Noveriera, Adinda Ayu; Sahadewa, Sukma; Andiani, Andiani (Universitas Wijaya Kusuma Surabaya, 2025)
Background: The incidence of low birth weight babies (LBW) is important because it is an indicator to measure a child's health status, and until now it is still one of the health problems generally faced by developing countries, including Indonesia. One of the risk factors for LBW is the level of hemoglobin (Hb). Hemoglobin is a parameter that is widely used to determine the prevalence of anemia. Objective: The purpose of this study was to analyze the relationship between hemoglobin levels of pregnant women and the incidence of low birth weight babies. Method: The research method used a cross-sectional design with a sample size of 49 respondents who were taken by simple random sampling method after fulfilling the inclusion and exclusion criteria at the Ngegong, Mangunharjo and Demangan Health Centers, Madiun City. Result: Data obtained through the patient's medical record. Data analysis in this study using the Chi Square test obtained a p- value of 0.02 <0.05 and OR = 0.75. Conclusion: So it can be concluded that there is a relationship between low hemoglobin levels and the incidence of low birth weight, where low hemoglobin levels have a 0.75 times higher risk of experiencing LBW. The Spearman rank correlation coefficient value of 0.445 indicates the strength of the relationship between these two variables in the moderate category.